Different morphotypes of the tabby (EDA) dentition in the mouse mandible result from a defect in the mesio-distal segmentation of dental epithelium - Peterková, R; Kristenová, P; Lesot, H; Lisi, S; Vonesch, J L; Gendrault, J L; Peterka, M (Orthodontics & craniofacial research, 2002)
OBJECTIVES: Prenatal identification of the different dentition morphotypes, which exist in the lower molar region of tabby (Ta) adult mice, and investigation of their origin. The mouse Ta syndrome and its counterpart anhidrotic (hypohidrotic) ectodermal dysplasia (EDA) in human are characterized by absence or hypoplasia of sweat glands, hair and teeth. DESIGN: Analysis of tooth morphogenesis using serial histological sections and 3D computer aided reconstructions of the dental epithelium in the cheek region of the mandible. SETTING AND SAMPLE POPULATION: Institute of Experimental Medicine, Academy of Sciences, Prague. Heads of 75 Ta homozygous and hemizygous mice and 40 wild type (WT) control mice aged from embryonic day (ED) 14.0-20.5 (newborns), harvested during 1995-2001. OUTCOME MEASURE: Prenatal identification of five distinct morphotypes of Ta dentition on the basis of differences in tooth number, size, shape, position and developmental stage and of the morphology of the enamel knot in the most mesial tooth primordium. RESULTS: The mesio-distal length of the dental epithelium was similar in the lower cheek region in Ta and WT mice. In Ta embryos, there was altered the mesio-distal segmentation of the dental epithelium giving rise to the individual tooth primordia. Prenatally, two basic morphotypes I and II and their particular subtypes (Ia, Ib, Ic, and IIa, IIb, respectively) of the developing dentition were identified from day 15.5. The incidence of the distinct morphotypes in the present sample did not differ from postnatal data. The proportion of the morphotype I and II was dependent on mother genotype. CONCLUSION: The different dentition morphotypes in Ta mice originate from a defect in the mesio-distal segmentation of the dental epithelium in mouse embryos. This defect presumably leads to variable positions of tooth boundaries that do not correspond to those of the WT molars. One tooth primordium of Ta mice might be derived from adjacent parts of two molar primordia in WT mice.
Keywords: Genetic Diseases, X-Linked; abnormality zubů; odontometrie; zubní zárodek; Epithelium; Molar; Tooth Germ; počítačové zpracování obrazu; Disease Models, Animal; mužské pohlaví; odontogeneze; Mice; Ectodermal Dysplasia; Morphogenesis; Odontometry; moláry; Mice, Mutant Strains; mutantní kmeny myší; Mandible; modely nemocí na zvířatech; ženské pohlaví; hypohidróza; zvířata; Humans; ektodermální dysplazie; epitel; Tooth Abnormalities; myši; morfogeneze; mandibula; Image Processing, Computer-Assisted; Odontogenesis; Female; genetické nemoci vázané na chromozom X; Hypohidrosis; lidé; Male; Animals